Geophilus serbicus sp. nov., a new species from the Balkan Peninsula (Chilopoda: Geophilomorpha: Geophilidae) - Stojanović, Dalibor Z.; Mitić, Bojan M.; Gedged, Amna M.; Antić, Dragan Ž.; Makarov, Slobodan E. (Zootaxa, 2019)
Geophilus serbicus sp. nov., a new epigeic centipede species, is described and illustrated based on specimens collected from the Stara Planina Mountains (the Balkan Mountain Range), Eastern Serbia, Balkan Peninsula. Considerations on the taxonomic relationships with some similar Geophilus species are briefly presented, and the distribution of the new species is mapped.